2009
DOI: 10.1074/jbc.m109.011601
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Modulates the Pathogen Binding Ability of Dendritic Cells (DCs) by Down-regulation of DC-specific Intercellular Adhesion Molecule-3 Grabbing Non-integrin (DC-SIGN)

Abstract: MicroRNA-155 (miR-155) has been involved in the response to inflammation in macrophages and lymphocytes. Here we show how miR-155 participates in the maturation of human dendritic cells (DC) and modulates pathogen binding by downregulating DC-specific intercellular adhesion molecule-3 grabbing non-integrin (DC-SIGN), after directly targeting the transcription factor PU.1. During the maturation of DCs, miR-155 increases up to 130-fold, whereas PU.1 protein levels decrease accordingly. We establish that human PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
171
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 46 publications
11
171
0
Order By: Relevance
“…Transcription factor c-Fos as a target of miR-155 was negatively for moDC maturation (Dunand-Sauthier et al, 2011). Similarly for what was described for regulation of IL-6 by miR-155 (Ceppi et al, 2009;O'Connell et al, 2010;Dunand-Sauthier et al, 2011), a positive role for miR-155 in mouse moDC maturation is contrasted by a reported negative role of miR-155 for maturation of human moDC, at least based on DC-Sign expression (Martinez-Nunez et al, 2009). Maturation from monocytes into moDCs was also found to be correlated with decreased miR-211 (Lu et al, 2011a).…”
Section: Maturation From Monocytes Into Modcssupporting
confidence: 51%
See 1 more Smart Citation
“…Transcription factor c-Fos as a target of miR-155 was negatively for moDC maturation (Dunand-Sauthier et al, 2011). Similarly for what was described for regulation of IL-6 by miR-155 (Ceppi et al, 2009;O'Connell et al, 2010;Dunand-Sauthier et al, 2011), a positive role for miR-155 in mouse moDC maturation is contrasted by a reported negative role of miR-155 for maturation of human moDC, at least based on DC-Sign expression (Martinez-Nunez et al, 2009). Maturation from monocytes into moDCs was also found to be correlated with decreased miR-211 (Lu et al, 2011a).…”
Section: Maturation From Monocytes Into Modcssupporting
confidence: 51%
“…During LPS-mediated moDC maturation, miR-155 is up-regulated. In cell line with over-expressed miR-155, expression levels of transcription factor PU.1 and DC-SIGN was reduced (Martinez-Nunez et al, 2009). Suppression of miR-155 in moDCs increased DC-SIGN expression and improved the binding of HIV protein gp-120 and Candida albicans (Martinez-Nunez et al, 2009).…”
Section: Mirnas Regulate Effector Function By Modcsmentioning
confidence: 99%
“…Importantly, the pro‐inflammatory effects of miR‐155 during ACR implicate that it targets mRNAs coding for anti‐inflammatory proteins. Intriguingly, our mRNA arrays showed that the 33 dysregulated transcripts involved in the IL‐6 pathway also function downstream of SPI1 18, 25 an established target of miR‐155. Whereas the anti‐inflammatory transcription factor SPI1 decreased during ACR, miR‐155 inhibition de‐repressed SPI1.…”
Section: Discussionmentioning
confidence: 91%
“…SPI 1 is a distinct leukocytic miR‐155 target implicated in the repression of IL‐6 signaling 24 and acting as an inhibitor of dendritic cell pathogen binding and antigen presentation of dendritic cells to T cells 25. Splenic expression levels of SPI1 decreased in a time‐dependent way (Figure 2K).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation